Politik Hukum Kekuasaan Kehakiman Di Indonesia - Withyanti, Wira Paskah (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2020)
Along with the continued development of the political dynamics that occurred during the founding of the Republic of Indonesia has a significant impact on the survival and growth of judicial power. Initial ideas of placing the judicial authorities and the independent judiciary free from interference by other branches of power have a long history. In carrying out the duties of a judge must be able to manage skills and as an upholder of justice professional, kind and reliable. Since this is an important prerequisite. Because of the ebb and flow of political dynamics in Indonesia that today is a democratic state. Where Indonesia recently found his form when the reform introduced in 1998. A new independent judicial power can be realized in a more noticeable when the Suharto regime fell, and then transforms the Law No. 40 of 1970, and then followed by a change to the provisions of Article 24 of the Constitution of 1945. Political law is closely related to the judicial authorities and the judiciary is independent state authority to conduct judiciary, enforcing the law, and justice based on Pancasila, for the implementation of state laws in the Republic of Indonesia. Implementation of judicial power carried by a Supreme Court and judicial bodies underneath, which is the general courts, religious courts, military courts, administrative courts, and a Constitutional Court. Judicial power in Indonesia is an independent and independent authority charged with adjudicating and enforcing law and justice based on Pancasila and the 1945 Constitution.